Video Dokumenter "Sesanti Titi Luri Tengger" Sebagai Media informasi - Yogi Widya Saka Warsaa (Jurnal Desain Komunikasi Visual Asia, 2022)
Tengger Mountains that are around at Bromo Mount. The people are called Tenggerese. The Tenggerese live like "Sesanti Titi Luri" (following the footsteps of their ancestors or following the religion, beliefs, culture and customs of their ancestors from generation to generation). So every traditional ceremony that is carried out continues as carried out by its ancestors. The Tenggerese not only have the Yadnya Kasada ceremony as one of the identities attached to the Tengger people, but also have so many other traditional and religious ceremonies such as the Karo Ceremony, Unan-unan Ceremony, Kawulu Ceremony, Kapat Ceremony, Tawur Agung Kasanga Ceremony, Mayu Desa Ceremony. and many more traditional ceremonies of the Tenggerese that are still being carried out. This information media aims to convey what various ceremonies are carried out by the Tenggerese community through direct explanations from sources. In the research process, the data becomes primary data and secondary data. Primary data is the result of interviews conducted with several sources including; (a) interviews with Tengger culturalists to find out the history of the Tengger; (b) interview with Singgih Pandita Dukun Suku Tengger; (c) interviews with community elders of the Tenggerese. While secondary data is literature collected from various written sources. The results of the research resulted in a documentary video entitled "Sesanti Titi Luri Tengger" have duration of 25 minutes, and frame size 1080x1920 Pixels.